Scientific evidence on vitamin D supplementation in patients affected by COVID-19: an integrative bibliographic review - Rocha, Isaac Hidekishimada da Silva (2021)
The objective of this review was to assess the effects of vitamin D supplementation in patients affected by COVID-19. In the methodology, a survey was carried out by means of an electronic search in data banks LILACS, PubMed and Cochrane, by articles published in 2020 and 2021. In the initial electronic search, 241 articles were identified in the PubMed base, 68 articles in Cochrane and 3 articles in LILACS on the subject. In the first screening, 187 studies were selected and 125 were excluded by not presenting the words “covid” and “vitamin D”, not title and / or summary. In the second screening, 177 articles were excluded and 10 studies were selected for inclusion in the review. As a result, 4 two 10 included patients with mild COVID-19, while 2 involved patients in serious condition. In relation to life, a majority of two studies involve patients with advanced eating and comorbidities, such as diabetes and hypertension. As a conclusion, vitamin D supplementation is most effective in mild to moderate COVID-19 patients, mainly in patients who had vitamin supplementation before being treated for the disease. Regarding patients with severe COVID-19, the events will show that high doses can generate rapid and satisfactory effects, without time of hospitalization, therefore, or late start of supplementation can be a limiting factor.